1867 Ga. Code 873 - (:unkn) unknown (My University, 1866)
§ 4443: Prohibited deliberately challenging or accepting a duel with a sword, pistol, or other deadly weapon. Violators fined not less than five hundred dollars and imprisoned for any time not exceeding six months.
Keywords: DUELING